ANALISIS PENGARUH LITERASI KEUANGAN SYARIAH DAN RELIGIUSITAS PADA MINAT MENABUNG DI BANK SYARIAH ( STUDI KASUS MAHASISWA FEB PERBANKAN SYARIAH UNIVERSITAS ISLAM MALANG ) - Dandi M Ilham; Afifudin Afifudin; Arista Fauzi Kartika Sari (El-Aswaq: Islamic Economics and Finance Journal, 2022)
This study aims to determine the Analysis Of the Effect Of Sharia Financial Literature and Religiosity on interest in saves in Sharia Banks ( Case Study of FEB Sharia Banking Students in Malang Islamic University ). This type of research is quantitative research In this study the samples taken were Students Of FEB Sharia Banking University Islamic Malang, with a total of 100 students. Taking the number of samples using purposive sampling technique to get respondents. The analytical tool used is multiple linear regression analysis using SPSS. The results showed that the sig value was 0.000 and 0.000 <0.05, meaning it means that H1a and H2b are accepted. This means that the independent variable has a positive and partially significant effect on the interest in saving the dependent variable. This means that with the influence Of Islamic Financial Literacy and Religiosity in FEB Students Of Sharia Banking, Islamic University Of Malang